Nematic fluctuations in iron-oxychalcogenide Mott insulators - B. Freelon (Nature Portfolio, 2021)
Abstract Nematic fluctuations occur in a wide range physical systems from biological molecules to cuprates and iron pnictide high-T c superconductors. It is unclear whether nematicity in pnictides arises from electronic spin or orbital degrees of freedom. We studied the iron-based Mott insulators La2O2Fe2OM2M = (S, Se), which are structurally similar to pnictides. Nuclear magnetic resonance revealed a critical slowing down of nematic fluctuations and complementary Mössbauerr spectroscopy data showed a change of electrical field gradient. The neutron pair distribution function technique detected local C 2 fluctuations while neutron diffraction indicates that global C4 symmetry is preserved. A geometrically frustrated Heisenberg model with biquadratic and single-ion anisotropic terms provides the interpretation of the low temperature magnetic fluctuations. The nematicity is not due to spontaneous orbital order, instead it is linked to geometrically frustrated magnetism based on orbital selectivity. This study highlights the interplay between orbital order and spin fluctuations in nematicity.